Moral Value in David Ayer’s “Bright Home” - Fahlevi Reza Natsir; Gusti Ayu Made Rai Suarniti; Ni Nyoman Kertiasih (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
TThis study explores the moral values presented in David Ayer’s film